Molecular basis for substrate recognition by lysine methyltransferases and demethylases - Del Rizzo, Paul A.; Trievel, Raymond C. (Biochimica et biophysica acta, 2014)
Lysine methylation has emerged as a prominent covalent modification in histones and non-histone proteins. This modification has been implicated in numerous genomic processes, including heterochromatinization, cell cycle progression, DNA damage response, DNA replication, genome stability, and epigenetic gene regulation that underpins developmental programs defining cell identity and fate. The site and degree of lysine methylation is dynamically modulated through the enzymatic activities of protein lysine methyltransferases (KMTs) and protein lysine demethylases (KDMs). These enzymes display distinct substrate specificities that in part define their biological functions. This review explores recent progress in elucidating the molecular basis of these specificities, highlighting structural and functional studies of the methyltransferases SUV4-20H1 (KMT5B), SUV4-20H2 (KMT5C), and ATXR5, and the demethylases UTX (KDM6A), JMJD3 (KDM6B), and JMJD2D (KDM4D). We conclude by examining these findings in the context of related KMTs and KDMs and by exploring unresolved questions regarding the specificities and functions of these enzymes. This article is part of a Special Issue entitled: Methylation: A Multifaceted Modification — looking at transcription and beyond. •The active site structure of SUV4-20 KMTs enables selective H4K20me1 methylation.•ATXR5 monomethylates K27 through specific recognition of A31 in histone H3.1.•UTX and JMJD3 demethylate H3K27me3 through conserved specificity determinants.•Sequence variations in JMJD2 KDMs govern differential recognition of H3K36me3.